2013
DOI: 10.1051/0004-6361/201321592
|View full text |Cite
|
Sign up to set email alerts
|

Large scale IRAM 30 m CO-observations in the giant molecular cloud complex W43

Abstract: We aim to fully describe the distribution and location of dense molecular clouds in the giant molecular cloud complex W43. It was previously identified as one of the most massive star-forming regions in our Galaxy. To trace the moderately dense molecular clouds in the W43 region, we initiated W43-HERO, a large program using the IRAM 30 m telescope, which covers a wide dynamic range of scales from 0.3 to 140 pc. We obtained on-the-fly-maps in 13 CO (2-1) and C 18 O (2-1) with a high spectral resolution of 0.1 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 64 publications
4
85
0
Order By: Relevance
“…As the dust observations have no velocity resolution, we see all the dust and thus gas along the line of sight. Carlhoff et al (2013) showed that the Herschel dust data are similar within the uncertainties to the CO data at the velocity range of W43 (v LSR = 60−120 km s −1 ). Hence, the Herschel dust observations are dominated by the emission from W43 and the contributions of other regions along the line of sight can be neglected.…”
Section: H 2 Column Densitymentioning
confidence: 57%
See 1 more Smart Citation
“…As the dust observations have no velocity resolution, we see all the dust and thus gas along the line of sight. Carlhoff et al (2013) showed that the Herschel dust data are similar within the uncertainties to the CO data at the velocity range of W43 (v LSR = 60−120 km s −1 ). Hence, the Herschel dust observations are dominated by the emission from W43 and the contributions of other regions along the line of sight can be neglected.…”
Section: H 2 Column Densitymentioning
confidence: 57%
“…This region is situated at the intersection of the Galactic bar and the first spiral arm (Scutum-Centaurus Galactic arm, Nguyen Luong et al 2011;Carlhoff et al 2013), leading to complex kinematic structures and possibly high star formation activity. The complex W43 is referred to as a Galactic mini-starburst region (Motte et al 2003;Bally et al 2010) and shows a star formation rate of ∼0.1 M yr −1 (Nguyen Luong et al 2011) or 5−10% of the star formation rate in the entire Milky Way.…”
Section: Introductionmentioning
confidence: 99%
“…Probability distribution functions of CO (Goldsmith et al 2008;Goodman et al 2009) are clipped at higher column densities owing to a high optical depth. Only recently has a special method been developed to obtain an H 2 map from 13 CO and C 18 O observations in W43 that suffers less from a cut-off at high column densities (Carlhoff et al 2013). However, all methods are still subject to other uncertainties, such as the variable CO/H 2 conversion factor or the variation in excitation temperature T ex (see Fig.…”
Section: Line-of-sight Confusion In Continuum Mapsmentioning
confidence: 99%
“…However, all methods are still subject to other uncertainties, such as the variable CO/H 2 conversion factor or the variation in excitation temperature T ex (see Fig. 11 in Carlhoff et al 2013 that shows how the PDF shifts by changing only a few Kelvin T ex ).…”
Section: Line-of-sight Confusion In Continuum Mapsmentioning
confidence: 99%
“…The Herschel key program HOBYS (see Motte et al 2010Motte et al , 2012 identifies ridges as high-density filaments, above 10 23 cm −2 in colFinal IRAM/PdBI FITS cube is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/570/A15 umn density, which is favorable to the formation of high-mass (OB-type, ≥8 M ) stars (see Hill et al 2011;Nguyen Luong et al 2011a;Hennemann et al 2012). The most extreme of these ridges, W43-MM1, lies in the massive, highly concentrated and very dynamic W43 molecular complex located at 6 kpc (Nguyen Luong et al 2011b;Carlhoff et al 2013). In its central region, W43-MM1 is thought to be experiencing a cloud collision , causing a remarkably efficient burst of high-mass star formation (Motte et al 2003).…”
Section: Introductionmentioning
confidence: 99%